Who is Malala Yousafzai?- Biography - Brown, Dinah; Thomson, Andrew (Children's book illustrator) (New York, New York : Grosset & Dunlap, an imprint of Penguin Random House, 2015)
Malala Yousafzai was a girl who loved to learn but was told that girls would no longer be allowed to go to school. She wrote a blog that called attention to what was happening in her beautiful corner of Pakistan and realized that words can bring about change. She has continued to speak out for the right of all children to have an education. In 2014 she won the Nobel Peace Prize.
Includes bibliographical references (pages 104-105).
Keywords: Yousafzai, Malala, -- 1997- -- Juvenile literature; Yousafzai, Malala, -- 1997-; Taliban -- Juvenile literature; Taliban; Girls -- Education -- Pakistan -- Juvenile literature; Girls -- Violence against -- Pakistan -- Juvenile literature; Women social reformers -- Pakistan -- Biography -- Juvenile literature; Girls -- Education -- Pakistan; Girls -- Violence against -- Pakistan; Reformers; Women -- Biography; Pakistan -- Social conditions -- Juvenile literature; Pakistan -- Social conditions; Biographies